Effect of Sexual Counseling Training in Gynecological Cancers According to the PLISSIT Model on Midwifery Students' Awareness and Attitude A Randomized Clinical Trial - Demirhan Kayacik, Ahsen (International journal of community based nursing and midwifery, 2024)
Copyright: © International Journal of Community Based Nursing and Midwifery.